1997
DOI: 10.1039/a605417j
|View full text |Cite
|
Sign up to set email alerts
|

Cation complexation by chemically modified calixarenes. Part 10. Thioamide derivatives of p-tert-butylcalix[4]-, [5]- and [6]-arenes with selectivity for copper, silver, cadmium and lead. X-Ray molecular structures of calix[4]arene thioamide–lead(II) and calix[4]arene amide–copper(II) complexes

Abstract: The effect of chemical modification of the lower rim of p-tert-butylcalix[4]-, [5]-and [6]-arenes has beenanalysed with respect to cation binding by thioamide podands. Extraction data for metal picrates from water into dichloromethane are discussed. Cu II , Pb II and Ag I ions are extracted efficiently by all the thioamides studied, whereas extraction of Cd II only reaches significant levels with the pentamer derivative. Unlike their calixarene amide counterparts, these thioamides have no affinity in extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 20 publications
3
35
0
Order By: Relevance
“…Thiocarbamoyl groups [159,160] or dithiocarbamoyl groups when attached to the calixarene skeleton such as in ligand 30 [161,162] provide selectivity for Ag + , Pd 2+ , Hg 2+ and other 'soft' metal ions over 'hard' ones.…”
Section: Silver Ion Recognitionmentioning
confidence: 99%
“…Thiocarbamoyl groups [159,160] or dithiocarbamoyl groups when attached to the calixarene skeleton such as in ligand 30 [161,162] provide selectivity for Ag + , Pd 2+ , Hg 2+ and other 'soft' metal ions over 'hard' ones.…”
Section: Silver Ion Recognitionmentioning
confidence: 99%
“…Here, we present four new calix [4]thioamide ionophores design with the aim of using them as active material in Pb(II)-selective electrodes and compound 2, known earlier [13,14]. The structure of the studied ligands are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 98%
“…Tetrakis(diethyl)thioamide 2 is known as good Pb(II)-extractant but also for Cu 2þ and Ag þ cations [13]. The crystal structure of its complex with lead was already published [14]. It was revealed that Pb 2þ cation is bonded by four ethereal oxygen atoms and four sulfur atoms of the thiocarbonyls.…”
Section: Introductionmentioning
confidence: 97%
“…The corresponding Cu(II) species feature non-coordinating anions, such as PF À 6 , ClO À 4 , and NO À 3 , and have thus far eluded structural characterization. Moreover, the number of reports on the solid state structures of calixarene-derived copper(II) complexes is scarce [11][12][13][14][15]. Herein we report the preparation, spectroscopic properties, and solid state structure of a new organic-inorganic hybrid polymer with dinuclear Cu(II) linear connectors linked by the ditopic pro-ligand L 1 [16] (Scheme 1, R = H).…”
mentioning
confidence: 95%